Access, access, access: the Three A's of pulmonary rehabilitation – perspectives of patients, loved ones and healthcare professionals. Issue 2 (3rd May 2022) - Marques, Alda; Souto-Miranda, Sara; Dias, Cláudia; Melo, Elsa; Jácome, Cristina
Improving access to pulmonary rehabilitation (PR) is a worldwide priority [1]. Evidence suggests that those who are more symptomatic, with frequent hospitalisations and whose health status and ability to exercise and perform activities of daily living is worse, are also the ones who respond better [2] and should be referred/prioritised to PR [3]. We explored whether these criteria are aligned with the perspectives of people with chronic respiratory diseases (CRDs), their loved ones (LOs) and healthcare professionals (HCPs). Efforts need to be made to increase access to pulmonary rehabilitation as early as possible, prioritising those who are more symptomatic and have functional status limitations, and improving communication within and among healthcare services https://bit.ly/3LMcLcU